(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The components present in the essential oils extracted from Anaphalis margaritacea (L.) Benth., Salvia leucantha Cav. and Thymus linearis Benth. were identified by GC and GC/MS analysis. The main compounds present in the oils were aromadendrene (20.0%) in S. leucantha, Phellandrene (12.5%), α-thujene (12.0%) in A. margaritacea and thymol (50.0%) in T. linearis. The antibacterial activity of all the three oils against E. coli, P. aeruginosa, S. aureus and S. typhi, has been studied. In the antibacterial activity S. typhi is the most resistant bacteria to all the tested oils whereas essential oil of T. linearis showed highest antibactericidal activity against S. aureus in diffusion method.